The Influence of The Characteristics of The Management Accounting Information System On Managerial Performance at PT. Pos Indonesia (Persero) In Lombok - Apsasi, Melsa; Santoso, Budi; Arni Muhsyaf, Saipul (Devotion : Journal of Research and Community Service, 2023)
The characteristics of the management accounting information system become one of the important factors in helping to improve managerial performance in an enterprise. This study aims to analyze the influence of the characteristics of management accounting information systems in terms of broad scope, timeliness, aggregate, and integration aspects on managerial performance. The object used in this study is PT POS Indonesia (Persero) in Lombok with a population of 145 employees. The sampling technique uses pusposive sampling which is selected by 110 employees as respondents based on specified criteria. This research uses quantitative methods with primary data types. Data collection techniques using questionnaires. The results showed that of the four characteristics of the management accounting information system, only from the aspect of timeliness which has a positive influence on managerial performance while from the broad scope, aggregate, and integration aspects, it has no influence on managerial performance.